Improved Survival With Surgical Treatment of Primary Lung Lesions in Non-Small Cell Lung Cancer With Brain Metastases: A Propensity‐Matched Analysis of Surveillance, Epidemiology, and End Results Database - Wang, Qing; Li, Jing; Liang, Xiaohua; Zhan, Qiong (Frontiers in Oncology, 2022)
Objectives: Non-small cell lung cancer (NSCLC) with Brain metastases (BM) is an advanced disease with poor prognosis and low survival rate. Our study evaluated the survival benefit of primary lung resection with mediastinal lymph node dissection in NSCLC patients with BM using Surveillance, Epidemiology, and End-result (SEER) databases. Methods: A total of 15,703 patients with BM of NSCLC diagnosed from 2010 to 2016 were analyzed. Patients (N=203) patients who underwent radical surgical treatment for primary lung lesions and patients (N=15500) who did not undergo surgery were compared. We successfully analyzed patients using propensity score matching (PSM). Kaplan‐Meier and Cox‐ regression analyses were applied to assess prognosis. Results: The median survival in the surgery group was longer than in the control group (27 months vs 5 months; P < 0.001) in the overall sample, 21 months longer compared to the control group (27 months vs 6 months; P<0.001) in a PSM cohort. Cox regression analysis showed that underwent surgery patients in the propensity-matched sample had a significantly lower risk of mortality (HR:0.243, 95%CI: 0.162-0.365, P＜0.001) compared with untreated patients. Multivariate analysis identified the following as independent risk factors for NSCLC with BM: no primary resection surgery, age >65 years, worse differentiation, squamous cell carcinoma, lymphatic metastasis, no systemic therapy. Subgroup analysis revealed that radical resection of the primary lung provided a survival benefit regardless of marital status, tumor size, tumor grade, tumor T stage, and mediastinal lymph node metastasis after PSM. Conclusion: Radical resection of primary lung can improve the survival of NSCLC patients with BM. Male, age＞65 years old, poorly differentiated tumor, tumor size＞5cm, and mediastinal lymph node metastasis were factors for poor survival.